Case Report: Co-occurrence of Duchenne Muscular Dystrophy and Frontometaphyseal Dysplasia 1 - Kim, Jaewon; Lee, Dong-Woo; Jang, Ja-Hyun; Kim, Myungshin; Yim, Jisook; Jang, Dae-Hyun (Frontiers in Pediatrics, 2021)
Herein, we present a rare case of co-occurring Duchenne muscular dystrophy (DMD) and frontometaphyseal dysplasia 1 (FMD1), two different X-linked diseases, in a 7-year-old boy. He presented with proximal muscle weakness and elevated creatine phosphokinase levels. A multiplex ligation-dependent probe amplification study of DMD revealed the de novo duplications of exons 2–37, thereby confirming the diagnosis of DMD. Initial evaluation revealed atypical features, such as facial dysmorphism, multiple joint contractures, and severe scoliosis, at an early age. However, these were overlooked and were assumed to be atypical manifestations of DMD. Then, the patient’s maternal cousin was diagnosed with FMD1 with pathogenic missense variant in FLNA (NM_001110556.2: c.3557C>T/p.Ser1186Leu). A family genetic test revealed that the patient and his mother had the same pathogenic variant in FLNA. The patient’s atypical manifestations were considered symptoms of FMD1. Therefore, if one disease does not fully explain the patient’s clinical features, an expanded genetic study is needed to detect coincidental disease.